Activism within music education: working towards inclusion and policy change in the Finnish music school context. Issue 1 (11th January 2016) - Laes, Tuulikki; Schmidt, Patrick
Abstract : This study examines how interactions between policy, institutions and individuals that reinforce inclusive music education can be framed from an activist standpoint. Resonaari, one among many music schools in Finland, provides an illustrative case of rather uncommonly inclusive practices among students with special educational needs. By exploring this case, contextualised within the Finnish music school system, we identify the challenges and opportunities for activism on micro, meso and macro levels. On the basis of our analysis, we argue that Resonaari's teachers are proactive because, within an inclusive teaching and learning structure, they act in anticipation of future needs and policy changes, engaging in what we call teacher activism. We claim that this type of activism is key for inclusive practices and policy disposition in music education.